Exploring the Rare Coexistence of Expanded Dengue Syndrome and Wilson Disease in Acute Liver Failure: A Case Series (Bangladesh Critical Care Journal, 2025)
Dengue fever, a viral infection transmitted by the Aedes mosquito, is common in tropical and subtropical regions. It is frequently linked to severe complications, including acute liver failure. Wilson disease is a rare hereditary illness that impacts copper metabolism, can also lead to fulminant hepatic failure, and is a well-known cause of acute liver failure in young adults. The simultaneous occurrence of both dengue and Wilson disease is extremely rare, posing significant challenges in diagnosis and treatment. This case series explores the complexities of diagnosing and managing acute liver failure in patients with expanded dengue syndrome, who were subsequently diagnosed with Wilson disease.Bangladesh Crit Care J September 2025; 13 (2): 115-119